Theorizing Homophobia - Adam, Barry D. (Sexualities, 1998)
A series of contemporary theories that have been used to explain homophobia are assessed. Structural, feminist, comparative, gender panic, queer, and socio-historical theories rely on the premises of a diverse set of scholarly disciplines, and in turn, generate their own objects of analysis, whether `homophobia', `heterosexism', or `heteronormativity'. While the current flourishing of gay and lesbian studies has generated important insights into the workings of homophobia, analyses have also tended to be limited and fragmentary. This paper suggests a study of homophobic projects that combines theoretical tools able to recognize experience, discourse, structure, and history.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; homophobie; hétéronormativité; hétérosexisme; premier cycle; queer; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques

Des droits à reconnaître: les lesbiennes face à la discrimination - Bonneau, Micheline; Demczuk, Irène (Collection Les Entêtées, 1998)
Regroupant recherches et analyses, témoignages et récits personnels, ce livre rend compte de la discrimination vécue par les lesbiennes. Malgré que le Québec ait adopté une Charte des droits de la personne qui interdit toute discrimination basée sur l'orientation sexuelle, il faut reconnaître que l'adoption de ce principe d'équité n'a pas fait disparaître toute trace d'hétérosexisme dans la société. Les lesbiennes ne bénéficient pas encore d'une égalité juridique formelle, encore moins réelle.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; lesbophobie; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; shm4000; soc2014; sociologie; systèmes d'oppressions; thématiques; violences